2017
DOI: 10.1016/j.tranpol.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Scale, quality and efficiency in road maintenance: Evidence for English local authorities

Abstract: ReuseThis article is distributed under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs (CC BY-NC-ND) licence. This licence only allows you to download this work and share it with others as long as you credit the authors, but you can't change the article in any way or use it commercially. More information and the full terms of the licence here: https://creativecommons.org/licenses/ Takedown If you consider content in White Rose Research Online to be in breach of UK law, please notify us by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…With respect to efficiency studies, Wheat (2017) undertakes the first study of local road maintenance costs in Britain and utilised a forerunner of the dataset under consideration in this paper. The author considered the optimal scale of operation as well as evidence for the cost efficiency of local highway authorities.…”
Section: Application To Highways Maintenance Costs In Englandmentioning
confidence: 99%
“…With respect to efficiency studies, Wheat (2017) undertakes the first study of local road maintenance costs in Britain and utilised a forerunner of the dataset under consideration in this paper. The author considered the optimal scale of operation as well as evidence for the cost efficiency of local highway authorities.…”
Section: Application To Highways Maintenance Costs In Englandmentioning
confidence: 99%
“…Firstly, the literature has identified that road maintenance is subject to economies of scale. For instance, Wheat (2017) analyzes the efficiency in road maintenance for 51 local authorities in England and finds that sharing maintenance services (or mergers) across small local authorities would lead to potential cost savings. Moreover, there is, on average, scope for 17% cost savings without compromising maintenance quality and level of traffic flow.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Whilst there has been a long history of efficiency benchmarking in the roads sector, econometric techniques have been little applied (see Nash, 2018); though there has been recent developments in the literature focusing on the application of econometric methods to assess the relative efficiency performance in local authority roads in Great Britain (see Wheat, 2017), and also interest from the Office of Rail and Road in Great Britain in applying such approaches to strategic roads (see KPMG, 2016). Our paper therefore contributes new empirical evidence to a relatively limited but emerging international literature focused on comparing the efficiency of road maintenance and renewal activities.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the problem is that the economies of scale can be different for new construction of roads (cf. Verhoef and Mohring, 2009) and for their subsequent maintenance and operation, where it is known that road length often, but not always, is associated with lower unit costs (Blom-Hansen, 2003;Wheat, 2017).…”
Section: Risksmentioning
confidence: 99%